Health education program in improving knowledge regarding emergency contraception among school teachers in Duhok - Abdulmalek, Iman Yousif; Ibrahim, Wahida A. (AL-Kindy College Medical Journal, 2016)
Background: Emergency contraception (EC) is a general term used to describe drugs and devices that are utilized to prevent pregnancy following unprotected intercourse or in the event of contraceptive failure. This postcoital birth-control option is available by means of hormonal pills or copper-bearing intrauterine device.Objectives: The objectives of the study were to assess the women's knowledge regarding EC, to compare the knowledge of school teachers with other women in the community, as well as assessing the pre-post test knowledge of teachers.Type of the study: A cross sectional and quasi- experimental study.Methods: It was carried out in Duhok during the period from 20th of November 2014 to 6th of January 2015. A Simple and systematic methods of sampling was used to collect 600 married women in their reproductive age group (15-49 years old ), 300 visitors from Primary health Care Centers, and 300 from school teachers.Results: showed that (77%) of study sample were used a natural (withdrawal) contraceptive way, while (3%) heard about emergency contraceptive, (13.2%) of them had unintended pregnancy and (1.2%) had an experience of induced abortion. From those who heard about emergency contraception (2.7%) considered the hormonal pills were the methods of emergency contraceptive and the friends were the source of information in (1.5%). In addition, there is a highly significant difference between the teacher's knowledge in pre and post-test .Conclusions: Our community knowledge toward EC is low, and there is a good benefit after doing the education program about the information regarding emergency contraception